Pola Musiman dan Antar Tahunan Salinitas Permukaan Laut Di Perairan Utara Jawa-Madura - Ahmad Najid; John I Pariwono; Dietriech G Bengen; Subhat Nurhakim; Agus S Atmadipoera (UNIVERSITAS SRIWIJAYA, 2012)
ABSTRACTWatermass of Java Sea is already known having a strongly connection with monsoon system in Indonesian region. Study of temperature valiability for and/or its relation to exploitation of marine and coastal resources have been done by scientists before hand. But the salinity condition is rare to studied, while the characteristic is important to the real life application. The sea surface salinity data archive, is primarily used in this study, is a monthly average within January 1994 – December 2010 by a spatial resolution of 1o x1o. Dataset of wind from ECMWF as a secondary parameter, have been monthly averages both for east-west (zonal) component and north-south (meridional) component, it is derived from 10 meters above sea level within period of January 1994 – December 2010, by a spatial resolution of 2.5o x 2.5o. Descriptive analysis have been done in order to get a complete picture of the SSS seasonal fluctuation. The results shows that SSS in Java Sea having a seasonal variability, which indicated by appearences of two SSS maximum and two SSS minimum annualy. Based on monthly average in the northern part of Java-Madura Seas, the SSS is haveing range of 32,0 PSU – 34,4 PSU. In the first transitional monsoon (Maret-April-Mei), SSS is relatively lower than others, i.e. NW monsoon, SE monsoon, and the second transitional monsoon, where it is found a core low SSS consentrated in the western part of Java Sea and also in south of Makassar strait.Keywords: Sea surface salinity, seasonal fluctuation, wind monsoon system, Java sea ABSTRAKMassa air Laut Jawa telah diketahui memiliki hubungan yang erat dengan sistem muson di Indonesia. Kajian variabilitas temperatur terhadap dan/atau keterkaitannya dengan pemanfaatan sumberdaya laut dan pesisir juga telah banyak dilakukan. Sedangkan untuk kondisi salinitas belum banyak dikaji, padahal secara aplikasi adalah penting untuk diketahui karakteristiknya. Data arsip Salinitas Permukaan Laut (SSS), digunakan sebagai data primer dalam penelitian ini, merupakan rerata bulanan dari Januari 1994 – Desember 2010 dengan resolusi spasial 1o x1o. Data angin yang bersumber dari ECMWF sebagai data sekunder merupakan rerata bulanan untuk komponen timur-barat (zonal) dan komponen utara selatan (meridional) pada ketinggian 10 meter di atas permukaan laut dari Januari 1994 – Desember 2010, dengan resolusi spasial 2,5o x 2,5o. Analisa deskriptif dilakukan untuk menghasilkan pemahaman yang komplit. Hasil kajian menunjukkan bahwa SSS di perairan Laut Jawa memilik variabilitas antar musim yang diindikasikan dengan dua puncak SSS maksimum dan dua lembah SSS minimum dalam setahun. Berdasarkan rerata bulanan pada tahun 1994 – 2010 di Laut Utara Jawa-Madura, SSS berkisar antara 32,0 PSU – 34,4 PSU. Musim peralihan I (Maret-April-Mei) SSS relatif terendah dibandingkan pada musim yang lain, yakni musim barat, musim timur, dan musim peralihan II, dimana SSS rendah terkonsentrasi di bagian timur laut Jawa, di selatan Selat Makasar.Kata kunci: salinitas permukaan laut, fluktuasi musiman, sistem angin muson, Laut Jawa